Predicting the risk of atherosclerotic cardiovascular disease among adults living with HIV/AIDS in Addis Ababa, Ethiopia: A hospital-based study - Woldu, Minyahil; Minzi, Omary; Shibeshi, Workineh; Shewaamare, Aster; Engidawork, Ephrem (PloS one, 2021)
Atherosclerotic Cardiovascular Disease (ASCVD) is an emerging problem among People living with HIV/AIDS (PLWHA). The current study aimed at determining the risk of ASCVD among PLWHA using the Pooled Cohort Equation (PCE) and the Framingham Risk score (FRS). A hospital-based study was carried out from January 2019 to February 2020 in PLWHA. The prevalence of ASCVD risk was determined in individuals aged between 20 to 79 and 40 to 79 years using the FRS and PCE as appropriate. Chi-square, univariate and multivariate logistic regressions were employed for analysis. The prevalence of high-risk ASCVD for subjects aged 20 and above using both tools was 11.5 %. For those aged 40 to 79 years, PCE yielded an increased risk (28%) than FRS (17.7%). Using both tools; advanced age, male gender, smoking, and increased systolic blood pressure were associated with an increased risk of ASCVD. Younger age (adjusted odds ratio, AOR) 0.20, 95%CI: 0.004, 0.091; P< 0.001), lower systolic blood pressure (AOR 0.221, 95%CI: 0.074, 0.605 P< 0.004), and lower total cholesterol (AOR 0.270, 95%CI: 0.073, 0.997; p<0.049) were found to be independent predictors of reduced risk of ASCVD. Likewise, younger age (40 to 64 years), female gender, and lower systolic blood pressure were significantly associated with lower risk of ASCVD among patients aged 40 to 79 years using both PCE and FRS. A considerable number of PLWHA have been identified to be at risk for ASCVD. ASCVD risk was significantly associated with advanced age, male gender, higher blood pressure, and smoking using both FRS and PCE. These factors should therefore be taken into account for designing management strategies.